Nuclear pore proteins are involved in the biogenesis of functional tRNA. - Simos, Geōrgios; Tekotte, Hildegard; Grosjean, Henri; Segref, Alexandra; Sharma, Kishore; Tollervey, David; Hurt, Ed (The EMBO journal, 1996)
Los1p and Pus1p, which are involved in tRNA biogenesis, were found in a genetic screen for components interacting with the nuclear pore protein Nsp1p. LOS1, PUS1 and NSP1 interact functionally, since the combination of mutations in the three genes causes synthetic lethality. Pus1p is an intranuclear protein which exhibits a nucleotide‐specific and intron‐dependent tRNA pseudouridine synthase activity. Los1p was shown previously to be required for efficient pre‐tRNA splicing; we report here that Los1p localizes to the nuclear pores and is linked functionally to several components of the tRNA biogenesis machinery including Pus1p and Tfc4p. When the formation of functional tRNA was analyzed by an in vivo assay, the los1(‐) pus1(‐) double mutant, as well as several thermosensitive nucleoporin mutants including nsp1, nup116, nup133 and nup85, exhibited loss of suppressor tRNA activity even at permissive temperatures. These data suggest that nuclear pore proteins are required for the biogenesis of functional tRNA.